Seedling emergence and growth of basil varieties under saline conditions - Reyes-Pérez, Juan José; Murillo-Amador, Bernardo; Nieto-Garibay, Alejandra; Troyo-Diéguez, Enrique; Reynaldo-Escobar, Inés María; Rueda-Puente, Edgar Omar (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The basil presents variability in the tolerance to salt stress and it is considered a sensitive plant to the salinity at the beginning of the growing period. In this study the effect of NaCl on basil emergence and growth was investigated by subjecting twenty varieties to 3 salinity levels: 0, 50 and 100 mm of NaCl, in a completely randomized design with 4 replications. The variables measured were emergence rate and percentage, radicle length, plantlet height, fresh and dry biomass of radical and of aerial part. Thai showed the greatest emergence percentage while Sweet Genovese and Napoletano exhibited the smallest ones. Thai also showed the highest emergency rate and Sweet Genovese the lowest rate. Sweet Dani, Thai, Italian Large Leaf and Net Rubin presented the maximum radicle length, while Sweet Dani, Italian Large Leaf, Dolly and Emily showed the largest fresh and dry biomass of radicle. Sweet Dani, Licorice, Genovese and Napoletano had the maximun plantlet height, while Sweet Genovese, Thai and Dolly had the largest fresh and dry biomass of aerial part. The different varieties response to NaCl in the plantlets emergency is discussed.